Land use, water management - Nagy, János (Acta Agraria Debreceniensis, 2012)
Due to the prognosed population increase to 9.2 billion people by 2050, the world’s crop production does not have any other chance than to increase production. This demand is a huge challenge for agriculture. Based on the forecasts, the growth rate of production of the main cereals will decrease as a result of the effect of soil, water, the increasing fuel and fertiliser prices and the impacts of climate change. Methods ensuring sustainability have to be preferred. Precision agriculture is the most effective method of crop production. We have to apply minimum cultivation in order to protect the soil surface, maintain its moisture content and increase its water reception ability. In addition to the localised use of fertiliser, sowing seed, irrigation and pesticides, it is also important to apply them in a targeted way on the basis of plot imaging. The use of the new technology results in significant cost saving and it could also reduce environmental load.